Make or Buy Analysis Model Based on Tolerance Design to Minimize Manufacturing Cost and Quality Loss - Rosyidi, Cucuk Nur; Akbar, Reza Rizkichani; Jauhari, Wakhid Ahmad (Makara Journal of Technology, 2014)
In a manufacturing company, manufacturing costs, or component prices, and tolerance will affect the price and the quality of a product. Companies must produce high-quality products with low manufacturing costs in order to keep their products competitive in the market; however, it is difficult to produce a high-quality product with a low manufacturing cost. Companies have difficulties in determining the components to be produced using their own manufacturing facilities (make) or outsourced to their suppliers (buy). Hence, a make or buy analysis is needed to minimize the manufacturing costs and quality loss and to determine the optimum alternative regarding make or buy decisions. This paper discusses an optimization model of a make or buy analysis for a manufacturing company in order to minimize the manufacturing costs and the quality loss in terms of manufacturer and customer quality loss. A numerical example is provided to show the application of the model using a simple assembly product consisting of three components. There are two machines that can be used to produce the components and three alternatives of suppliers to fulfill the order. Each machine and supplier have different characteristics in terms of manufacturing costs and its tolerance.